Investigation of the Relationship between Nursing and Midwifery Students' Self-Perceptions of Leadership Behaviors and Decision-Making Styles - Buket Hüseyniklioğlu; Fatma Tüysüz (Association of Nurse Managers, 2023)
Aim: The aim of this study is to examine the relationship between nursing and midwifery students' self-perceptions about leadership behaviors and their decision-making styles. The secondary aim is to examine the relationship between nursing and midwifery students' self-perceptions of leadership behavior and decision-making styles according to various demographic variables. Method: The research was carried out with 217 students studying in two programs, nursing and midwifery, in the School of Nursing at university in the Turkish Republic of Northern Cyprus. A personal information form, the "Melbourne decision-making scale I and II" and the "Self-Perception Scale of Undergraduate Students' Leadership Behaviors" were used collect data. Results: A significant difference was found between the programs studied and the decision-making styles and leadership behaviors of the students, as well as age and class. A significant and positive relationship was found between students' self-esteem scores in decision making and the results obtained from self-confident, principled and determined leadership behaviors (p<0.05). In addition, it was revealed that there is a statistically significant relationship between decision-making styles and leadership characteristics. Conclusion: It was revealed that as the self-esteem of nursing and midwifery students increased at all grade levels, leadership behaviors increased, as careful decision-making increased, leadership characteristics decreased, and when avoidant and panic decision-making increased, leadership behaviors increased. Leadership behaviors of both senior midwifery and nursing students were found to be higher than in other classes. In addition, it has been determined that midwifery students prefer to make procrastinating decisions and their leadership behaviors increase as the class and age of the students increase.